Genetic status, source and establishment risk of the giant tiger shrimp (penaeidae: penaeus monodon), an invasive species in colombian caribbean waters (2015)
The tiger shrimp (Penaeus monodon) is an Indo-Pacific species. Its global production between 1970 and 1980 exceeded all other shrimp species, which favored its introduction and cultivation outside its natural range in several countries of Africa, Europe, USA and South America. It is currently found in the coast of the Atlantic Ocean (Mexico, United States, Puerto Rico, Brazil, Guyana, Venezuela and Colombia). Despite the risk involved, no studies have been conducted to evaluate their impact as a possible invasive species and their genetic condition. This study evaluated the genetic status and population origin of P. monodon in the northernmost Colombian Caribbean, analyzing the mitochondrial DNA control region (mtDNA-CR). 16 individuals were randomly collected from Golfo de Salamanca and 342 original Indo-Pacific sequences were obtained from GenBank. Parameters of genetic diversity and genetic relationships were analyzed. There were a total of 358 sequences compared and 303 haplotypes identified. Three haplotypes were identified in the Colombian population. This results showed lower genetic diversity compared with Indo-Pacific populations. These haplotypes were closely related to those found in samples from the Philippines and Taiwan. We discuss the need to create a regional network to characterize the established populations in the Great Caribbean, with the purpose of inferring colonization processes and the establishment of management measures.Estado genético, origen y riesgo de establecimiento del camarón tigre gigante (Penaeidae: Penaeus monodon), una especie inavasora en aguas del Caribe colombianoEl camarón tigre (Penaeus monodon) es una especie del Indo-Pacífico. Su producción mundial entre 1970 y 1980 superó todas las otras especies de camarón, lo que favoreció su introducción y cultivo fuera del área de distribución natural en varios países de África, Europa, EE.UU. y América del Sur. Actualmente se encuentra en la costa del Océano Atlántico (México, Estados Unidos, Puerto Rico, Brasil, Guyana, Venezuela y Colombia). A pesar del riesgo que implica, no se han realizado estudios para evaluar su impacto como posible especie invasora y su condición genética. Este estudio evaluó el estado genético y el origen de la población de P. monodon en el norte del Caribe colombiano, analizando la región control del ADN mitocondrial (ADNmt-CR). 16 individuos fueron recolectados al azar del Golfo de Salamanca y 342 secuencias originales de muestras del Indo- Pacífico fueron obtenidas de GenBank. Se analizaron los parámetros de diversidad genética y las relaciones genéticas. Se analizaron un total de 358 secuencias y se identificaron 303 haplotipos. En la población de Colombia se identificaron tres haplotipos, mostrando una baja diversidad genética en comparación con las poblaciones del Indo-Pacífico. Estos haplotipos se encontraron cercanamente relacionados con secuencias obtenidas de muestras de Filipinas y Taiwán, principalmente. Se discute la necesidad de crear una red regional para caracterizar las poblaciones establecidas en el Gran Caribe, con el propósito de inferir los procesos de colonización y el establecimiento de medidas de manejo